2022
DOI: 10.7759/cureus.23378
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Utilization and Adverse Drug Reaction Profiling in Patients With Schizophrenia at a Tertiary Care Hospital in Western India

Abstract: Introduction Prescription pattern studies conducted in patients with schizophrenia have shown variability in the utilization of antipsychotics based on the geographical location of the study setting. Moreover, there is only a sparse number of studies specifically related to adverse drug reactions (ADRs) in schizophrenia. Hence, a need was felt to study the antipsychotic utilization pattern and adverse drug reactions in patients with schizophrenia in our setting. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study conducted in the psychiatry OPD of a tertiary care hospital in Andhra Pradesh and Mumbai revealed that Olanzapine and Risperidone respectively were currently most used for Schizophrenia. 14,15 However, Olanzapine is associated with dose related lowering seizure threshold and worsens diabetes by impairing glucose tolerance. It is associated with metabolic complications and high risk of stroke in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the psychiatry OPD of a tertiary care hospital in Andhra Pradesh and Mumbai revealed that Olanzapine and Risperidone respectively were currently most used for Schizophrenia. 14,15 However, Olanzapine is associated with dose related lowering seizure threshold and worsens diabetes by impairing glucose tolerance. It is associated with metabolic complications and high risk of stroke in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there were no ADRs among any older adults who used quetiapine in combination with escitalopram. Fourth, the majority of ADRs were mild [32] and preventable [33]. Psychiatrists have taken pDDIs seriously, and have prevented ADRs by controlling drug doses, strengthening monitoring, and taking measures in advance.…”
Section: Discussionmentioning
confidence: 99%